1966
DOI: 10.1111/j.1748-1716.1966.tb03179.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Picrotoxin on Stretch‐Activated Post‐Synaptic Inhibitions in Spinal Motoneurones

Abstract: The effects of picrotoxin on post‐synaptic inhibitions were intracellularly investigated in cat popliteal, common peroneal and hamstring motoneurones which were activated by stretch of the triceps surae, tibialis anterior or semitendinosus muscles. In some experiments a single electrical shock to the nerve was also used as a stimulus. Inhibitions from muscle stretch were studied by the following criteria: i) hyperpolarization of the post‐synaptic membrane, ii) decrease in size of the monosynaptic excitatory po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For instance bicuculline blocks the inhibitory effects of GABA at mammalian motoneurones (Curtis et al, 1971) and the present results have shown that picrotoxin and bicuculline can antagonize the hyperpolarizing effect of GABA at amphibian motoneurones. The observation of a picrotoxin sensitive component of post-synaptic inhibition at cat motoneurones (Kellerth & Szumski, 1966) supports the possibility of a post-synaptic inhibitory transmitter role for GABA in mammals. However, a picrotoxin or bicuculline-sensitive post-synaptic inhibition of motoneurones in amphibians has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 56%
“…For instance bicuculline blocks the inhibitory effects of GABA at mammalian motoneurones (Curtis et al, 1971) and the present results have shown that picrotoxin and bicuculline can antagonize the hyperpolarizing effect of GABA at amphibian motoneurones. The observation of a picrotoxin sensitive component of post-synaptic inhibition at cat motoneurones (Kellerth & Szumski, 1966) supports the possibility of a post-synaptic inhibitory transmitter role for GABA in mammals. However, a picrotoxin or bicuculline-sensitive post-synaptic inhibition of motoneurones in amphibians has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 56%
“…The modulation of the MSR by GABA A receptors is mediated by two mechanisms: presynaptic inhibition of Ia afferent terminals and postsynaptic inhibition of motoneurones (Kellerth & Szumski, 1966; Schmidt, 1971; Peng & Frank, 1989; Jonas et al 1998; Rudomin & Schmidt, 1999; Kullmann et al 2005). Despite the morphological and pharmacological evidence available on GABA A receptors on the motoneurones, the role of these receptors in the postsynaptic modulation of the MSR has been scarcely studied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these may be part of a monosynaptic monoaminergic pathway from the reticular formation and medulla oblongata to motoneurones (Dahlstrom & Fuxe, 1965). It is possible that the strychnine resistant, picrotoxin sensitive inhibitions described by Kellerth & Szumski (1966) were adrenergic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that picrotoxin does not influence the inhibition of Purkinje cells in the cerebellum (Crawford, Curtis, Voorhoeve & Wilson, 1963) or inhibitions in the spinal cord (Curtis, 1963). Kellerth & Szumski (1966), on the other hand, were able to show that picrotoxin abolished strychnine resistant inhibitions of spinal cord motoneurones and its ability to block several types of inhibitory junction in invertebrates is well documented (Robbins & Van der Kloot, 1958;Robbins 1959;Grundfest, Reuben & Rickles, 1959;Usherwood & Grundfest, 1964). J. W. PHILLIS AND A. K. TEBECIS Picrotoxin also blocks the inhibitory actions of y-aminobutyric acid (GABA) at crustacean neuromuscular junctions.…”
Section: Discussionmentioning
confidence: 99%